Minimally Invasive Approach to Congenital Lung Malformations: A Comparative Study of Thoracoscopic Resection Techniques - Gul, Sarooj; Fayaz, Afnan; Khattak, Aizaz; Zeb, Mian Rahmat; Tahir, Dawood; Khan, Muhammad Daraz; Khan, Adnan; Tahir, Imran (Indus Journal of Bioscience Research, 2024)
Introduction: Congenital lung malformations (CLMs), encompassing a diverse range of pulmonary anomalies, are increasingly diagnosed in children due to advancements in prenatal imaging and early postnatal screening techniques.Objective: The main objective of the study is to find a clinical comparative study of thoracoscopic anatomical lesion resection and lobectomy in the treatment of congenital lung malformations in childrenMethodology: This comparative study was conducted at Hayatabad medical complex Peshawar from January 2024 to June 2024. Data were collected from 285 patients. Data included detailed demographic information such as the age, gender, and weight of each patient at the time of surgery.Results: The duration of surgery was significantly longer in Group A (130 ± 20 minutes) compared to Group B (90 ± 15 minutes). Intraoperative blood loss was lower in Group A (50 ± 10 mL) compared to Group B (120 ± 30 mL). Intraoperative complications were minimal, with only one complication in Group A (0.7%) and none in Group B (0%).In the comparison between Group A (Thoracoscopic Lesion Resection) and Group B (Lobectomy), Group A showed a significantly shorter hospital stay (4.2 ± 0.5 vs. 6.8 ± 0.8 days, p < 0.01) and quicker chest tube removal (2.1 ± 0.4 vs. 3.6 ± 0.6 days, p < 0.05). Postoperative pain levels were lower in Group A, with fewer air leaks (5% vs. 12%, p < 0.05) and recurrent respiratory infections (8% vs. 15%, p < 0.05).Conclusion: In conclusion, this study demonstrates that thoracoscopic anatomical lesion resection is a highly effective and lung-sparing approach for the treatment of congenital lung malformations in children. The study has several limitations also, In children, the importance of particularly lung maturation makes it necessary to save as much healthy lung tissue as possible for a child with this disease.